Yunnan Baiyao Inhibits Periodontitis by Suppressing the Autophagic Flux - Yanjie Li; Wang Liu; Ruoyu Zhao; Yuanyuan An; Mingzhu Zhang; Xiaobin Ren; Hongbing He (Elsevier, 2024)
Background: Yunnan Baiyao (YNBY), a traditional Chinese medicine, is renowned for its anti-inflammatory properties. Recent studies have suggested that YNBY plays a significant role in inhibiting osteoclast differentiation and autophagy, which are essential processes in inflammation and bone resorption associated with periodontitis. However, the precise relationship between autophagy and the mechanism by which YNBY inhibits osteoclastogenesis remains unexplored.The primary objective of this study was to investigate the inhibitory effects of YNBY on the process of osteoclastogenesis and its potential in preventing inflammatory bone loss. Methods: The animals were subjected to sacrifice at intervals of 2, 4, and 6 weeks postintervention whilst under deep anaesthesia, and specimens were subsequently collected. The specimens were subjected to hematoxylin and eosin (HE) staining, in addition to tartrate-resistant acid phosphatase (TRAP) staining and subsequently imaged employing a digital scanner. The confirmation of osteoclast (OC) differentiation and autophagic flux was achieved through various techniques, including western blotting, transmission electron microscopy (TEM), TRAP staining, pit formation assay, and immunofluorescence. Results: The microcomputed tomography images provided evidence of the effective inhibition of alveolar bone absorption at 2, 4, and 6 weeks following YNBY treatment. Additionally, the histomorphometric evaluations of tissue segments stained with HE and TRAP, which involved measuring the distance between the alveolar bone crest (ABC) and cementoenamel junction (CEJ) and quantifying TRAP-positive OCs, yielded comparable results to those obtained through computed tomography analysis. YNBY treatment resulted in a decrease in the CEJ-ABC distance and inhibition of OC differentiation. Furthermore, in vitro studies showed that the autophagy modulators rapamycin (RAP) and 3-methyladenine (3-MA) significantly affected OC differentiation and function. YNBY attenuated the impact of RAP on the differentiation of OCs, autophagy-related factor activation, and bone resorption. Conclusions: We hypothesise that YNBY suppresses the differentiation of OC and bone resorption by blocking autophagy. This study reveals that targeting autophagy might be a new alternative treatment methodology for periodontitis treatment.